[Zaha Hadid] (Casas, 2020)
Contiene: L'Avenue Libertador - Esfera City Center - D'Leedon - Alai - 520 West 28 th - Capital Hill Residence - City Life Milano Residential Complex - Torre residencial Mayfair - One Thousand Museum